Spatio-temporal variability of Borer Polychaetes in Posidonia oceanica beds and its relation to meadow structure - VASAPOLLO, C.; VILLANO, L.; GAMBI, M. C. (Mediterranean Marine Science, 2014)
Posidonia oceanica forms an extremely productive and complex ecosystem in the coastal Mediterranean Sea providing a suitable habitat for hundreds of plant and animal species. Among motile invertebrates associated to Posidonia meadows, polychaete borers of the plant sheaths represent a unique group which exploit a peculiar microhabitat. They belong to the family Eunicidae with three dominant species, Lysidice collaris, L. ninetta and L. unicornis. Due to their strong association with Posidonia shoots, these animals are particularly suitable to study the plant and animal spatial relationships and their pattern of variability. The aim of this work was to evaluate the frequency of occurrence of these animals (Index of Borer, IB) at different spatial and temporal (summer vs winter) scales in two Posidonia meadows off the Ischia Island (Gulf of Naples, Italy), which are exposed to different degrees of human impact and of hydrological conditions. Results showed IB values of L. collaris (the most abundant species) significantly different between meadows and at scales from 10s to 100s of meters, as well as between summer and winter. The IB of L. ninetta showed significant differences only at scales of 10s of meters while, on the contrary, the IB of L. unicornis (the less abundant species) did not show variability at any spatial and temporal scales. Most of the variance was at the more impacted and less water movement exposed meadow, suggesting higher level of small and intermediate scales of patchiness of borers at this meadow. These variation patterns are discussed in relation to local environmental differences between the studied Posidonia beds.